(untitled) (Research, Society and Development, 2021)
Immigrants arriving in Brazil face many challenges and difficulties. Between them are language proficiency and cultural assimilation, which directly impact their social inclusion process and their quality of life. Therefore, a project was elaborated, whose objective was to help immigrants in the welcoming process, which consisted mainly of free classes in Portuguese language and Brazilian culture. We sought to answer how extension projects can contribute to the social inclusion of Haitian immigrants in the western region of the state of Paraná, Brazil. This is a qualitative work, whose methodology consists of a simple idea of knowledge sharing, between tutors and participants, through a questionnaire answered by 27 participants to obtain the data. Concludes that the extension projects have powerful impacts on the lives of Haitian immigrants, thus assisting the process of social inclusion through linguistic learning.